Tindak Tutur Ekspresif dalam Film Sejuta Sayang Untuknya karya Wiraputra Basri - Windi Rostanti; Ngusman Abdul Manaf (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2023)
Exspressive speech act play an innportant role in the portrayal of the characters of the story characters, but they have not have not been studied much in films. This study aims to analyze the types of expressive speech acts and the context of the use of speech strategies in expressive speech acts in the film Sejuta Sayang Untuk Karya Wiraputra Basri. This research uses descriptive qualitative research methods. The source of this research data is the expressive speech act in the film Sejuta Sayang Untuknya Karya Wiraputra Basri. In collecting data, this research was carried out in two techniques, namely listening and recording techniques. After that, data identification is carried out which is classified as a type of expressive speech act and the context for the use of speech strategies. The results showedothat9there0are 8 types ofuexpressive speech acts, namely saying thank you, apologizing, praising, insinuating, congratulating, complaining, insinuating, and insulting. The dominant expressive speech act used is to say thank you. In the context of speech (=K+S) dominant using speech strategy (SBTBKP); in the context of speech (K+S) uses a lot of speech strategies (SBTBKN); in the context of petutur (+K-S) uses a lot of speech strategies (SBTBKP); in the context of speech (-K-S) uses a lot of speech strategies (SBTBB); in the context of (-K+S) many use speech strategies (SBTBKP, SBTBKN and SBSS).